Differences in microbial diversity and environmental factors in ploughing-treated tobacco soil - Zhang, Yuzhen; Bo, Guodong; Shen, Minchong; Shen, Guoming; Yang, Jianming; Dong, Shanyu; Shu, Zhaohe; Wang, Zhaobao (Frontiers in Microbiology, 2022)
During agricultural production, ploughing affects the existing traits of the planted soil, including environmental factors (physicochemical properties and soil enzymatic activity) and microbial community, but whether deep tillage and conventional tillage cause differences in soil microecology is unknown. In this study, the 16S rRNA high-throughput sequencing technology was combined with soil environmental factor detection to analyze the differences in microbial diversity of smokey soils at different depths. As the results, the composition and structure of microbial community varied in different of soil depth after ploughing. Two dominant phyla, Actinobacteria and Acidobacteria, have varied a lot between the deep-ploughing treatment HS3 (the sample in 10-20 cm depth after deep-ploughing treatment) sample and the conventional tillage HC3 (treatment the sample in 10-20cm depth after conventional tillage) sample. The abundance of Actinobacteria has increased significantly, while the abundance of Acidobacteria has decreased significantly. Moreover, deep tillage increased the activity of sucrase (S-SC) and nitrate reductase (NR) in samples with soil depth below 20 cm. In summary, deep tillage disturbed spatial microbial diversity and environmental factors significantly. This would provide new guidance for improving farmland management strategies, optimizing the activation methods of soil layers, further improving crop planting soil and increasing crop yield.